Answer:
The equation which is correct for the given function is:
D. [tex]y+2=2(x+3)^2[/tex]
Step-by-step explanation:
By looking at the graph we observe that the graph of the function passes through the point (-4,0) , (-2,0) , (-3,-2)
A)
[tex]y=(x+4)(x+2)[/tex]
when x= -3 we have:
[tex]y=(-3+4)(-3+2)\\\\y=1\times (-1)\\\\y=-1\neq -2[/tex]
Hence, option: A is incorrect.
B)
[tex]y=x^2+3x-2[/tex]
when x= -2 we have:
[tex]y=(-2)^2+3\times (-2)-2\\\\y=4-6-2\\\\y=-4\neq 0[/tex]
Hence, option: B is incorrect.
C)
[tex]y+2=-2(x+3)^2[/tex]
when x= -2 we have:
[tex]y+2=-2(-2+3)^2\\\\y+2=-2[/tex]
[tex]y=-4\neq 0[/tex]
Hence, option: C is incorrect.
D)
[tex]y+2=2(x+3)^2[/tex]
We see that the graph of this equation matches the given graph of the function.